Cross Immunological reaction between Nocardia asteroides and Salmonella typhimurium in mice: Muhamed Juweed Alwan,Maysoon Sabah Abbas, Sahar Hasan Ali and Zanab Abd Alzahra - Alwan, Muhamed Juweed (The Iraqi Journal of Veterinary Medicine, 2008)
The aim of this study was carried out to demonstrate the cross-immunitybetween Nocardia asteroids and Salmonella typhimurium antigens in mice.18 mice, from both sex,were randomally divided into three groups equally.the first group immunized subcutaneously with 0.0 5 micrometer / animal ofNocardia asteroids antigen and abooster dose of the same antigen wasinjected after week of the first dose. The second group was treated as thefirst group with Salmonella typhimurium antigen. .The third group wasserved as non-immunized control group. Delayed hypersensitivity and tubeagglutination test were checked at 30 days post-immunization. By usingNocardin and Sallmonelin antigens.The results revealed that the animals were immunized with Nocardiaantigens given agood immune response against nocardin and sallmonelin andalso those animal were immunized with Salmonella antigens showedimmune response against nocardin and sallmonelin antigen ,this may beindicated across- protection between Nocardia andSalmonella antigen .